Diffusion of Technologies by the Tikonko Agricultural Extension Centre (TAEC) to Farmers of the Tikonko Chiefdom in Sierra Leone: Impacts, Problems, Proposed Solutions, and an Updated Outlook - Samba Moriba; Joseph B.A. Kandeh; M. Craig Edwards (Journal of International Agricultural and Extension Education, 2011)
Sierra Leone is a west African nation with about two-thirds of its population engaged in agriculture but it cannot feed itself. The country’s agricultural activities were disrupted by a decade-long Civil War that created a great need for improved farming technologies. The Tikonko Agricultural Extension Centre (TAEC) operates in the Tikonko Chiefdom to assist local farmers in improving food production through the fabrication of farm tools to be adopted and used by farmers. This study was conducted to investigate the impacts of the TAEC’s technologies on farmers and their communities in the Tikonko Chiefdom and identify problems and solutions associated with the technologies and their diffusion. The target population included farmers (N = 318) who used TAEC’s technologies and TAEC staff (N = 18) who were involved in the diffusion process. A majority of the farmers adopted and used TAEC’s technologies readily, which they perceived had considerable impact on their farming practices and communities. The relevance of TAEC’s technologies to farmers in Tikonko Chiefdom was also evident. However, the participating farmers and TAEC staff encountered numerous problems. A majority agreed that the diffusion and adoption process could be improved by increasing the farmers’ access to loans. Providing appropriate technologies that can be adopted by low income farmers stands to increase their productivity and self-reliance while improving their nations’ food security. It is undeniable that technologies contributing to food sufficiency and alleviating poverty are needed throughout the developing world; policymakers must be reminded of this condition continually.
Keywords: Extension; Farming; Post-conflict; Sierra Leone; Technological Innovations